Blueberries Improve Endothelial Function in Postmenopausal Women With Above-Normal Blood Pressure via Reductions in Oxidative Stress. (14th June 2022) - Woolf, Emily; Litwin, Nicole; Terwood, Janee; Vazquez, Allegra; Ketelhut, Nathan; Michell, Kiri; Smith, Brayden; Grabos, Lauren; Lee, Sylvia; Ghanem, Nancy; Rao, Sangeeta; Sayec, Melanie Le; et al.
Abstract: Objectives: Research suggests blueberries and their (poly)phenols may improve endothelial dysfunction, a major risk factor for cardiovascular disease (CVD). The objective of this study was to investigate the impact of consuming 22 g/day for 12 weeks of freeze-dried highbush blueberry powder on endothelial function and other measures of cardiovascular health, oxidative stress, and circulating (poly)phenol metabolites in postmenopausal women with above-normal blood pressure. Methods: We performed a randomized, double-blind, placebo-controlled, parallel-arm trial in estrogen-deficient postmenopausal women aged 45–65 years with elevated blood pressure or stage 1-HTN. Endothelial function was assessed as brachial artery flow-mediated dilation (FMD) and normalized to individual shear rate area under the curve (FMD/SRAUC ) to control for inter-individual variability in reactive hyperemia-induced shear stress. To assess whether improvements in FMD were mediated by reduced oxidative stress, FMD was assessed before and after intravenous infusion of a supra-physiologic dose of ascorbic acid. Blood pressure, arterial stiffness, and plasma (poly)phenol metabolites were also assessed. Results: A total of 43 women completed the trial ( n  = 32 for endothelial function). Compliance in the Blueberry and Placebo groups were 93% and 91%, respectively. Mean total plasma (poly)phenol metabolite concentrations were increased at 4 (250, 053 nmol/L, P < 0.05) and 8 (303, 053 nmol/L, P < 0.05) weeks in the Blueberry group compared to baseline (125, 798 nmol/L) with a strong trend at 12 weeks (227, 971 nmol/L, P < 0.05), and no changes in Placebo. Blood pressure and arterial stiffness were unchanged with both treatments. At 12 weeks, FMD/SRAUC was increased by 96% from baseline ( P < 0.05) in the Blueberry group but unchanged in Placebo, and changes in FMD/SRAUC from baseline to 12 weeks were higher ( P < 0.05) than Placebo. The response in FMD/SRAUC to ascorbic acid infusion was lower ( P < 0.05) at 12 weeks compared to baseline in the Blueberry group but not Placebo. Conclusions: These findings suggest blueberries improve endothelial function, and is mediated, in part, by reduced oxidative stress in postmenopausal women with above-normal blood pressure, a high-risk population for developing CVD. Funding Sources: US Highbush Blueberry Council and USDA National Institute of Food and Agriculture.